Notch‐Expanded Murine Hematopoietic Stem and Progenitor Cells Mitigate Death from Lethal Radiation and Convey Immune Tolerance in Mismatched Recipients. (13th September 2016) - Milano, Filippo; Merriam, Fabiola; Nicoud, Ian; Li, Jianqiang; Gooley, Ted A.; Heimfeld, Shelly; Imren, Suzan; Delaney, Colleen
Abstract: The hematopoietic syndrome of acute radiation syndrome (h‐ARS) is characterized by severe bone marrow aplasia, resulting in a significant risk for bleeding, infections, and death. To date, clinical management of h‐ARS is limited to supportive care dictated by the level of radiation exposure, with a high incidence of mortality in those exposed to high radiation doses. The ideal therapeutic agent would be an immediately available, easily distributable single‐agent therapy capable of rapid in vivo hematopoietic reconstitution until recovery of autologous hematopoiesis occurs. Using a murine model of h‐ARS, we herein demonstrate that infusion of ex vivo expanded murine hematopoietic stem and progenitor cells (HSPCs) into major histocompatibility complex mismatched recipient mice exposed to a lethal dose of ionizing radiation (IR) led to rapid myeloid recovery and improved survival. Survival benefit was significant in a dose‐dependent manner even when infusion of the expanded cell therapy was delayed 3 days after lethal IR exposure. Most surviving mice (80%) demonstrated long‐term in vivo persistence of donor T cells at low levels, and none had evidence of graft versus host disease. Furthermore, survival of donor‐derived skin grafts was significantly prolonged in recipients rescued from h‐ARS by infusion of the mismatched expanded cell product. These findings provide evidence that ex vivo expanded mismatched HSPCs can provide rapid, high‐level hematopoietic reconstitution, mitigate IR‐induced mortality, and convey donor‐specific immune tolerance in a murine h‐ARS model. Stem Cells Translational Medicine 2017;6:566–575